Обґрунтування параметрів кілець короткозамкненого ротора при комплексному проектуванні асинхронного двигуна за квазітривимірним польовим аналізом і імітаційним моделюванням - Попович, Олександр Миколайович; Головань, Іван Васильович; Поліщук, Валентина Омельянівна (НТУ "ХПІ", 2019)
Для цілей підвищення енергоефективності асинхронних двигунів у складі електромеханічних систем, на прикладі насосної установки, обгрунтовано застосування уточненої математичної моделі двигуна із інтеграцією її до імітаційної моделі електромеханічної системи, яка враховує нелінійні залежності параметрів заступної схеми, що визначено за результатами квазітривимірного польового аналізу. Досліджено вплив збільшення площі перетину короткозамикаючих кілець ротора на робочі і пускові характеристики двигуна. Обгрунтовано апроксимаційні залежності електромагнітних параметрів за зміни величини конструктивних параметрів.

To justify and apply an improved mathematical model of induction motors for solving problems of increasing their energy efficiency as part of electromechanical systems. To investigate the effect of increasing the cross-sectional area of the short-circuited rotor rings on the efficiency in the operating mode of the electromechanical system of the engine-mechanism, the multiplicity of starting current and torque. The use of a refined mathematical model of the engine when integrating it into a simulation model of an electromechanical system that takes into account the non-linear dependencies of the parameters of the equivalent circuit calculated from the results of a quasi-three-dimensional field analysis. With reduced requirements for starting torque, it is reasonable to use an improved mathematical model of the engine when determining the parameters of the rings of a short-circuited rotor. The effect of increasing the cross-sectional area of the short-circuited rotor rings on the engine operating and starting characteristics is investigated. The approximation dependences of the electromagnetic parameters as a function of the magnitude of the design parameters are substantiated.
Substantiation of the parameters of short-circuited rings for integrated design of an asynchronous motor using quasi-three-dimensional field analysis and modeling
Keywords: комплексне проектування; математична модель; робочі характеристики; пускові характеристики; induction motor; complex design; mathematical model